Eosinophil recruitment and activation: the role of lipid mediators - Luna-Gomes, Tatiana; Bozza, Patricia; Bandeira-Melo, Christianne (Frontiers in Pharmacology, 2013)
Eosinophils are effector cells that migrate toward several mediators released at inflammatory sites to perform their multiple functions. The mechanisms driving eosinophil selective accumulation in sites of allergic inflammation are well established and involve several steps controlled by adhesion molecules, priming agents, chemotactic and surviving factors. Even though the majority of studies focused on role of protein mediators like IL-5 and eotaxins, lipid mediators also participate in eosinophil recruitment and activation. Among the lipid mediators with distinguish eosinophil recruitment and activation capabilities are platelet activating factor (PAF) and the eicosanoids, including leukotriene B4, cysteinyl leukotrienes and prostaglandin D2. In this review, we focused on the role of these four lipid mediators in eosinophil recruitment and activation, since they are recognized as key mediators of eosinophilic inflammatory responses.